Composite material energy-saving door and window profile

By using composite material raw materials with specific ratios and braiding and injection processes to prepare composite door and window profiles, the problems of insufficient thermal insulation and aging resistance of existing profiles are solved, and higher mechanical and mechanical properties and longer service life are achieved .

CN118813041BActive Publication Date: 2025-02-11NINGBO JINHUA ALUMINUM IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411040918.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-02-11
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

The existing composite door and window profiles have problems such as poor thermal insulation performance, insufficient sealing performance, aging resistance and mechanical and mechanical properties that need to be improved.

Method used

Used from fiber yarn, fluorenone pyrimidin polyamide polycondenser, diphosphorus pentoxide, polyphosphoric acid, perfluoropropane-2,2-diyl)bis(4,1-phenylene)diacrylate Composite materials made of raw materials such as 2-acrylamide-2-methylpropanesulfonic acid and 2,4,6-trivinylboroxane are prepared by braiding and resin injection processes, and are subjected to high-temperature hardening treatment. .

Benefits of technology

The mechanical and mechanical properties, aging resistance and fatigue resistance of composite doors and windows profiles are improved, making it longer service life, simple process and convenient operation, and suitable for continuous large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a composite material energy-saving door and window profile, relates to the technical field of composite material profiles, and is made of the following raw materials by weight: 45-55 parts of fiber yarn, 30-40 parts of fluorenone pyrimidine polyamide condensation polymer, 0.5-1 parts of phosphorus pentoxide, 0.1-0.3 parts of polyphosphoric acid, 1-3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1-3 parts of 2-acrylamide-2-methylpropane sulfonic acid, 1-3 parts of 2,4,6-trivinyl cycloboroxane, 0.3-0.6 parts of initiator, 0.3-0.6 parts of antioxidant, and 0.8-1.5 parts of coupling agent. The composite material energy-saving door and window profile has sufficient mechanical properties, good aging resistance and fatigue resistance, and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material profiles, and in particular to a composite material energy-saving door and window profile. Background Art

[0002] With the gradual improvement of my country's environmental protection requirements and energy-saving level, passive house technology has been widely promoted and applied. Passive house doors and windows are required to have lower heat transfer coefficients and higher sealing. At present, most door and window materials on the market are mainly aluminum alloy, color steel, PVC material, and wood. They have more or less disadvantages such as heavy weight, easy corrosion, easy aging, inconvenient installation and maintenance, and long construction period. In addition, they generally have technical defects that need to be further improved in thermal insulation performance. It is in this situation that people began to explore the use of composite material profiles to prepare doors and windows. Composite material profiles have the advantages of light weight, high strength, corrosion resistance, anti-aging, easy installation and maintenance, and have a high market prospect in the field of door and window preparation.

[0003] Existing composite door and window profiles have more or less technical defects such as poor thermal insulation performance, insufficient sealing, aging resistance and mechanical properties need to be further improved, and fatigue life needs to be further extended. In order to solve the above problems, a Chinese invention patent with authorization announcement number CN110094137B discloses a composite material energy-saving door and window profile, which comprises an inner frame profile (1) made of a composite material composed of a non-metallic fiber reinforced resin matrix through an extrusion molding process, a reinforced heat insulation baffle (2), and an outer decorative profile (3) made of a material that meets the requirements of the use conditions. The cross section of the inner frame profile (1) is in an "H" shape, and an opening cavity (11) is arranged on both sides of the inner frame profile. The reinforced heat insulation baffle (2) is in the shape of a rectangular plate and is arranged at the opening of the opening cavity (11). The outer decorative profile (3) is arranged on both sides of the inner frame profile (1). The invention has a lower heat transfer coefficient and higher sealing performance. A variety of fireproof and heat-insulating materials can be filled in the door and window profile, so that the door and window profile has multiple functions of fire prevention, fire resistance, heat insulation and energy saving. A single piece is processed and manufactured, and multiple pieces are assembled. The profile manufacturing process is simple, the filling and assembly operation is convenient and fast, the production cost is low, and it is beneficial to energy saving and environmental protection. However, its main material, glass fiber reinforced polyurethane composite material, still has more or less technical defects such as insufficient mechanical properties and aging resistance, and the performance stability and fatigue resistance need to be further improved.

[0004] It can be seen that the development of a composite material energy-saving door and window profile with sufficient mechanical properties, good aging resistance and fatigue resistance, and long service life meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of energy-saving door and window profiles. Summary of the invention

[0005] The main purpose of the present invention is to provide a composite material energy-saving door and window profile with sufficient mechanical properties, good aging resistance and fatigue resistance, and long service life.

[0006] To achieve the above purpose, the present invention provides a composite material energy-saving door and window profile, which is made of the following raw materials in parts by weight: 45-55 parts of fiber yarn, 30-40 parts of fluorenone pyrimidine polyamide condensation polymer, 0.5-1 parts of phosphorus pentoxide, 0.1-0.3 parts of polyphosphoric acid, 1-3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1-3 parts of 2-acrylamido-2-methylpropane sulfonic acid, 1-3 parts of 2,4,6-trivinyl cycloboroxane, 0.3-0.6 parts of initiator, 0.3-0.6 parts of antioxidant, and 0.8-1.5 parts of coupling agent.

[0007] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.

[0008] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 164.

[0009] Preferably, the initiator is dibenzoyl peroxide.

[0010] Preferably, the preparation method of the fluorenone-based pyrimidine-based polyamide polycondensate comprises the following steps: adding 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid, and a catalyst to a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material to a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 120-130°C under normal pressure for 1-3 hours, then heating to 232-242°C, and performing a polycondensation reaction at 100-350 Pa for 12-22 hours, then cooling to room temperature, adjusting to normal pressure, precipitating in water, washing the crude product with ethanol for 3-6 times, and then placing it in a vacuum drying oven at 90-96°C to dry to constant weight to obtain a fluorenone-based pyrimidine-based polyamide polycondensate.

[0011] Preferably, the molar ratio of the 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid, catalyst and high boiling point solvent is 1:1:(0.8-1):(9-16).

[0012] Preferably, the catalyst is at least one of thiophosphonate, phosphorous acid, and thiophosphoramide; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is any one of nitrogen, helium, neon, and argon.

[0013] Preferably, the fiber yarn is any one of glass fiber yarn, boron fiber yarn, carbon fiber yarn, and basalt fiber yarn.

[0014] Preferably, the monofilament diameter of the fiber yarn is 7-16 μm.

[0015] Another object of the present invention is to provide a method for preparing the composite material energy-saving door and window profile, comprising the following steps:

[0016] Step S1, mixing the other raw materials except the fiber yarn uniformly by weight to obtain a mixed material, and dispersing the mixed material in an organic solvent to obtain a resin glue solution;

[0017] Step S2, weaving the fiber yarn through a weaving machine according to a preset profile structure;

[0018] Step S3, immersing the woven fiber cloth into the resin glue solution to perform resin injection;

[0019] Step S4, hardening: hardening the fiber cloth injected with resin through a mold at high temperature;

[0020] Step S5, molding: cutting, grinding, assembling and gluing the hardened fiber cloth in sequence.

[0021] Preferably, the mass ratio of the mixed material to the organic solvent in step S1 is (0.8-1.2):1.

[0022] Preferably, the organic solvent in step S1 is at least one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.

[0023] Preferably, the high temperature hardening treatment in step S4 is specifically: keeping warm at 95-125° C. for 2-6 hours, and then keeping warm at 175-185° C. for 0.8-3 hours.

[0024] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0025] (1) The preparation method of the composite material energy-saving door and window profile disclosed in the present invention has a simple preparation process, convenient operation and control, no need for special equipment, low capital investment, low energy consumption, high preparation efficiency and finished product qualification rate, low labor intensity, small impact on the environment, suitable for continuous large-scale production, and has high promotion and application value.

[0026] (2) The composite material energy-saving door and window profile disclosed in the present invention is made of the following raw materials in parts by weight: 45-55 parts of fiber yarn, 30-40 parts of fluorenone pyrimidine polyamide condensation polymer, 0.5-1 parts of phosphorus pentoxide, 0.1-0.3 parts of polyphosphoric acid, 1-3 parts of perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1-3 parts of 2-acrylamide-2-methylpropanesulfonic acid, 1-3 parts of 2,4,6-trivinylcycloboroxane, 0.3-0.6 parts of initiator, 0.3-0.6 parts of antioxidant, and 0.8-1.5 parts of coupling agent. Through the mutual cooperation between the raw materials, the manufactured profile has sufficient mechanical properties, good aging resistance and fatigue resistance, and long service life.

[0027] (3) The composite material energy-saving door and window profile disclosed in the present invention, the fluorenone-pyrimidine-based polyamide condensation polymer is prepared by 2,6-diamino-9h-fluorene-9-one and pyrimidine-4,6-dicarboxylic acid through condensation reaction, and fluorenone, pyrimidine and amide structures are introduced into the molecular chain at the same time. Under the multiple effects of electronic effect, steric effect and conjugation effect, these structures make the product have better mechanical properties, better aging resistance and fatigue resistance, and longer service life; under the catalytic action of phosphorus pentoxide and polyphosphoric acid, the fluorenone-pyrimidine-based The benzene ring on the polyamide polycondensate can react chemically with the sulfonic acid group on 2-acrylamide-2-methylpropane sulfonic acid; at the same time, the unsaturated olefinic bond on 2-acrylamide-2-methylpropane sulfonic acid can copolymerize with perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate and 2,4,6-trivinylcycloboroxine which also contain unsaturated olefinic bonds to form an interpenetrating network structure, making the internal structure of the material denser, and further improving the mechanical properties, air tightness, aging resistance and fatigue resistance.

[0028] (4) The composite material energy-saving door and window profile disclosed in the present invention has high flexibility in product design and can be adapted to more application scenarios through the reasonable selection of the preparation process. Through the profile structure design, a variety of fireproof and heat-insulating materials can be filled in the door and window profile to make the door and window profile have multiple functions such as fire prevention, fire resistance, heat insulation and energy saving. At the same time, it can also ensure the stability of product performance, thereby effectively extending its service life. DETAILED DESCRIPTION

[0029] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1

[0030] A composite material energy-saving door and window profile is made of the following raw materials in parts by weight: 45 parts of fiber yarn, 30 parts of fluorenone-pyrimidine-based polyamide condensation polymer, 0.5 parts of phosphorus pentoxide, 0.1 parts of polyphosphoric acid, 3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1 part of 2-acrylamido-2-methylpropanesulfonic acid, 1 part of 2,4,6-trivinylcycloboroxane, 0.3 parts of initiator, 0.3 parts of antioxidant, and 0.8 parts of coupling agent.

[0031] The coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 1010; and the initiator is dibenzoyl peroxide.

[0032] The preparation method of the fluorenone-based pyrimidine-based polyamide polycondensate comprises the following steps: adding 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid and a catalyst into a high boiling point solvent and mixing them evenly to obtain a mixed material; then adding the mixed material into a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 120° C. for 1 hour under normal pressure, then heating to 232° C., performing a polycondensation reaction at 100 Pa for 12 hours, and then cooling the mixture. to room temperature, adjusted to normal pressure, precipitated in water, washed the crude product 3 times with ethanol, and then dried in a vacuum drying oven at 90°C to constant weight to obtain a fluorenone-based pyrimidine-based polyamide condensation polymer; the molar ratio of the 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid, catalyst, and high boiling point solvent is 1:1:0.8:9; the catalyst is a thiophosphonate; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is nitrogen.

[0033] The fiber yarn is glass fiber yarn; the monofilament diameter of the fiber yarn is 7 μm.

[0034] A method for preparing the composite material energy-saving door and window profile comprises the following steps:

[0035] Step S1, mixing the other raw materials except the fiber yarn uniformly by weight to obtain a mixed material, and dispersing the mixed material in an organic solvent to obtain a resin glue solution;

[0036] Step S2, weaving the fiber yarn through a weaving machine according to a preset profile structure;

[0037] Step S3, immersing the woven fiber cloth into the resin glue solution to perform resin injection;

[0038] Step S4, hardening: hardening the fiber cloth injected with resin through a mold at high temperature;

[0039] Step S5, molding: cutting, grinding, assembling and gluing the hardened fiber cloth in sequence.

[0040] The mass ratio of the mixed material and the organic solvent in step S1 is 0.8:1; the organic solvent in step S1 is N-methylpyrrolidone; the high temperature hardening treatment in step S4 is specifically: keeping warm at 95°C for 2h, and then keeping warm at 175°C for 0.8h. Example 2

[0041] A composite material energy-saving door and window profile is made of the following raw materials in parts by weight: 47 parts of fiber yarn, 33 parts of fluorenone pyrimidine polyamide condensation polymer, 0.7 parts of phosphorus pentoxide, 0.15 parts of polyphosphoric acid, 1.5 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1.5 parts of 2-acrylamido-2-methylpropane sulfonic acid, 1.5 parts of 2,4,6-trivinyl cycloboroxane, 0.4 parts of initiator, 0.4 parts of antioxidant, and 1 part of coupling agent.

[0042] The coupling agent is silane coupling agent KH560; the antioxidant is antioxidant 168; and the initiator is dibenzoyl peroxide.

[0043] The preparation method of the fluorenone-based pyrimidine-based polyamide polycondensate comprises the following steps: adding 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid and a catalyst into a high boiling point solvent and mixing them evenly to obtain a mixed material; then adding the mixed material into a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 123° C. for 1.5 hours at normal pressure, then heating to 236° C., performing a polycondensation reaction at 150 Pa for 15 hours, and then cooling The mixture was cooled to room temperature, adjusted to normal pressure, precipitated in water, washed with ethanol for 4 times, and then dried in a vacuum drying oven at 92° C. to constant weight to obtain a fluorenone-based pyrimidine-based polyamide condensation polymer; the molar ratio of the 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid, catalyst, and high boiling point solvent was 1:1:0.85:11; the catalyst was phosphorous acid; the high boiling point solvent was dimethyl sulfoxide; and the inert gas was helium.

[0044] The fiber yarn is boron fiber yarn; the monofilament diameter of the fiber yarn is 11 μm.

[0045] A method for preparing the composite material energy-saving door and window profile comprises the following steps:

[0046] Step S1, mixing the other raw materials except the fiber yarn uniformly by weight to obtain a mixed material, and dispersing the mixed material in an organic solvent to obtain a resin glue solution;

[0047] Step S2, weaving the fiber yarn through a weaving machine according to a preset profile structure;

[0048] Step S3, immersing the woven fiber cloth into the resin glue solution to perform resin injection;

[0049] Step S4, hardening: hardening the fiber cloth injected with resin through a mold at high temperature;

[0050] Step S5, molding: cutting, grinding, assembling and gluing the hardened fiber cloth in sequence.

[0051] The mass ratio of the mixed material and the organic solvent in step S1 is 0.9:1; the organic solvent in step S1 is N,N-dimethylformamide; the high temperature hardening treatment in step S4 is specifically: keeping warm at 105°C for 3 hours and then keeping warm at 178°C for 1.5 hours. Example 3

[0052] A composite material energy-saving door and window profile is made of the following raw materials in parts by weight: 50 parts of fiber yarn, 35 parts of fluorenone-pyrimidine-based polyamide condensation polymer, 0.75 parts of phosphorus pentoxide, 0.2 parts of polyphosphoric acid, 2 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 2 parts of 2-acrylamido-2-methylpropanesulfonic acid, 2 parts of 2,4,6-trivinylcycloboroxane, 0.45 parts of initiator, 0.45 parts of antioxidant, and 1.2 parts of coupling agent.

[0053] The coupling agent is silane coupling agent KH570; the antioxidant is antioxidant 1076; and the initiator is dibenzoyl peroxide.

[0054] The preparation method of the fluorenone-based pyrimidine-based polyamide polycondensate comprises the following steps: adding 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid and a catalyst into a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material into a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 125° C. for 2 hours at normal pressure, then heating to 237° C., performing a polycondensation reaction at 220 Pa for 17 hours, and then cooling to room temperature, adjusted to normal pressure, precipitated in water, washed the crude product 4 times with ethanol, and then dried in a vacuum drying oven at 93° C. to constant weight to obtain a fluorenone-based pyrimidine-based polyamide condensation polymer; the molar ratio of the 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid, catalyst, and high boiling point solvent is 1:1:0.9:13; the catalyst is thiophosphoramide; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is neon.

[0055] The fiber yarn is carbon fiber yarn; the monofilament diameter of the fiber yarn is 12 μm.

[0056] A method for preparing the composite material energy-saving door and window profile comprises the following steps:

[0057] Step S1, mixing the other raw materials except the fiber yarn uniformly by weight to obtain a mixed material, and dispersing the mixed material in an organic solvent to obtain a resin glue solution;

[0058] Step S2, weaving the fiber yarn through a weaving machine according to a preset profile structure;

[0059] Step S3, immersing the woven fiber cloth into the resin glue solution to perform resin injection;

[0060] Step S4, hardening: hardening the fiber cloth injected with resin through a mold at high temperature;

[0061] Step S5, molding: cutting, grinding, assembling and gluing the hardened fiber cloth in sequence.

[0062] The mass ratio of the mixed material and the organic solvent in step S1 is 1:1; the organic solvent in step S1 is N,N-dimethylacetamide; the high temperature hardening treatment in step S4 is specifically: keeping warm at 115°C for 4 hours and then keeping warm at 180°C for 2 hours. Example 4

[0063] A composite material energy-saving door and window profile is made of the following raw materials in parts by weight: 53 parts of fiber yarn, 38 parts of fluorenone-pyrimidine-based polyamide condensation polymer, 0.9 parts of phosphorus pentoxide, 0.25 parts of polyphosphoric acid, 2.5 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 2.5 parts of 2-acrylamido-2-methylpropanesulfonic acid, 2.5 parts of 2,4,6-trivinylcycloboroxane, 0.55 parts of initiator, 0.55 parts of antioxidant, and 1.3 parts of coupling agent.

[0064] The coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570 in a mass ratio of 1:2:1; the antioxidant is a mixture of antioxidant 1010, antioxidant 168, antioxidant 1076 and antioxidant 164 in a mass ratio of 1:1:3:5; and the initiator is dibenzoyl peroxide.

[0065] The preparation method of the fluorenone-based pyrimidine-based polyamide condensation polymer comprises the following steps: adding 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid and a catalyst into a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material into a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 128°C for 2.5 hours at normal pressure, then heating to 240°C, performing a condensation reaction at 330 Pa for 21 hours, then cooling to room temperature, adjusting to normal pressure, and evaporating in water. The crude product was precipitated out, washed with ethanol for 6 times, and then placed in a vacuum drying oven at 95° C. to dry to constant weight to obtain a fluorenone-based pyrimidine-based polyamide condensation polymer; the molar ratio of the 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid, catalyst, and high boiling point solvent is 1:1:0.95:14; the catalyst is a mixture of thiophosphonate, phosphorous acid, and thiophosphoramide in a mass ratio of 1:1:2; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is argon.

[0066] The fiber yarn is basalt fiber yarn; the monofilament diameter of the fiber yarn is 15 μm.

[0067] A method for preparing the composite material energy-saving door and window profile comprises the following steps:

[0068] Step S1, mixing the other raw materials except the fiber yarn uniformly by weight to obtain a mixed material, and dispersing the mixed material in an organic solvent to obtain a resin glue solution;

[0069] Step S2, weaving the fiber yarn through a weaving machine according to a preset profile structure;

[0070] Step S3, immersing the woven fiber cloth into the resin glue solution to perform resin injection;

[0071] Step S4, hardening: hardening the fiber cloth injected with resin through a mold at high temperature;

[0072] Step S5, molding: cutting, grinding, assembling and gluing the hardened fiber cloth in sequence.

[0073] The mass ratio of the mixed material and the organic solvent in step S1 is 1.1:1; the organic solvent in step S1 is a mixture of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide in a mass ratio of 2:3:1:4; the high temperature hardening treatment in step S4 is specifically: keeping warm at 122°C for 5 hours, and then keeping warm at 183°C for 2.5 hours. Example 5

[0074] A composite material energy-saving door and window profile is made of the following raw materials in parts by weight: 55 parts of fiber yarn, 40 parts of fluorenone-pyrimidine-based polyamide condensation polymer, 1 part of phosphorus pentoxide, 0.3 parts of polyphosphoric acid, 3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 3 parts of 2-acrylamido-2-methylpropanesulfonic acid, 3 parts of 2,4,6-trivinylcycloboroxane, 0.6 parts of initiator, 0.6 parts of antioxidant, and 1.5 parts of coupling agent.

[0075] The coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 1010; and the initiator is dibenzoyl peroxide.

[0076] The preparation method of the fluorenone-based pyrimidine-based polyamide polycondensate comprises the following steps: adding 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid and a catalyst to a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material to a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 130°C for 3 hours under normal pressure, then heating to 242°C, performing a polycondensation reaction at 350 Pa for 22 hours, then cooling to room temperature, adjusting to normal pressure, precipitating in water, washing the crude product with ethanol for 6 times, and then drying it in a vacuum drying oven at 96°C to constant weight to obtain the fluorenone-based pyrimidine-based polyamide polycondensate; the molar ratio of the 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid, the catalyst and the high boiling point solvent is 1:1:1:16; the catalyst is a thiophosphonate; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is nitrogen.

[0077] The fiber yarn is glass fiber yarn; the monofilament diameter of the fiber yarn is 16 μm.

[0078] A method for preparing the composite material energy-saving door and window profile comprises the following steps:

[0079] Step S1, mixing the other raw materials except the fiber yarn uniformly by weight to obtain a mixed material, and dispersing the mixed material in an organic solvent to obtain a resin glue solution;

[0080] Step S2, weaving the fiber yarn through a weaving machine according to a preset profile structure;

[0081] Step S3, immersing the woven fiber cloth into the resin glue solution to perform resin injection;

[0082] Step S4, hardening: hardening the fiber cloth injected with resin through a mold at high temperature;

[0083] Step S5, molding: cutting, grinding, assembling and gluing the hardened fiber cloth in sequence.

[0084] The mass ratio of the mixed material and the organic solvent in step S1 is 1.2:1; the organic solvent in step S1 is N-methylpyrrolidone; the high temperature hardening treatment in step S4 is specifically: keeping warm at 125°C for 6 hours and then keeping warm at 185°C for 3 hours.

[0085] Comparative Example 1

[0086] A composite material energy-saving door and window profile is substantially the same as Example 1, except that 2,4,6-trivinyl cycloboroxine is not added, and p-phenylenediamine is used instead of 2,6-diamino-9h-fluorene-9-one.

[0087] Comparative Example 2

[0088] A composite material energy-saving door and window profile is basically the same as Example 1, except that (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate is not added, and terephthalic acid is used instead of pyrimidine-4,6-dicarboxylic acid.

[0089] In order to further illustrate the unexpected positive technical effects achieved by the products of each embodiment of the present invention, the composite material energy-saving door and window profiles prepared in each example were tested for relevant properties. The test results are shown in Table 1. The test method is as follows:

[0090] (1) Fatigue life: The tensile fatigue properties of composite energy-saving door and window profiles were evaluated by a dynamic fatigue testing machine, and the fatigue life of composite energy-saving door and window profiles was finally obtained. The specific test conditions were: temperature 75±2℃, frequency 30Hz, and tensile load 30MPa.

[0091] (2) Bending strength: Tested in accordance with GBT1449-2005-Test method for bending properties of fiber reinforced plastics.

[0092] (3) Anti-aging properties: Each product was placed in a heat aging box for artificial accelerated hot air aging at 85°C for 100 hours. The anti-aging properties were measured by the retention rate of bending strength after aging. The larger the retention rate, the better the anti-aging properties.

[0093] Table 1

[0094]

[0095] It can be seen from Table 1 that the composite energy-saving door and window profile disclosed in the embodiment of the present invention has better mechanical properties, fatigue resistance and anti-aging properties than the comparative example products, and the combined addition of 2,4,6-trivinyl cycloboroxine, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 2,6-diamino-9h-fluorene-9-one and pyrimidine-4,6-dicarboxylic acid is beneficial to improving the above properties.

[0096] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A composite material energy-saving door and window profile, characterized in that: The invention is made of the following raw materials in parts by weight: 45-55 parts of fiber yarn, 30-40 parts of fluorenone-pyrimidine-based polyamide condensation polymer, 0.5-1 parts of phosphorus pentoxide, 0.1-0.3 parts of polyphosphoric acid, 1-3 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1-3 parts of 2-acrylamido-2-methylpropanesulfonic acid, 1-3 parts of 2,4,6-trivinylcycloboroxine, 0.3-0.6 parts of initiator, 0.3-0.6 parts of antioxidant, and 0.8-1.5 parts of coupling agent; the initiator is dibenzoyl peroxide; the fiber yarn is any one of glass fiber yarn, boron fiber yarn, carbon fiber yarn, and basalt fiber yarn; the monofilament diameter of the fiber yarn is 7-16 μm; The preparation method of the fluorenone-based pyrimidine-based polyamide condensation polymer comprises the following steps: adding 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid and a catalyst into a high boiling point solvent and mixing them evenly to obtain a mixed material; then adding the mixed material into a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 120-130° C. under normal pressure for 1-3 hours, then heating to 232-242° C., and heating at 100-350° C. a for 12-22 hours, then cooled to room temperature, adjusted to normal pressure, precipitated in water, washed with ethanol for 3-6 times, and then dried in a vacuum drying oven at 90-96° C. to constant weight to obtain a fluorenone-based pyrimidine-based polyamide condensation product; the molar ratio of the 2,6-diamino-9h-fluorene-9-one, pyrimidine-4,6-dicarboxylic acid, catalyst, and high boiling point solvent is 1:1:(0.8-1):(9-16).

2. The composite energy-saving door and window profile according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.

3. The composite energy-saving door and window profile according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010 , antioxidant 168 , antioxidant 1076 , and antioxidant 164 .

4. The composite energy-saving door and window profile according to claim 1, characterized in that: The catalyst is at least one of thiophosphonate, phosphorous acid, and thiophosphoramide; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is any one of nitrogen, helium, neon, and argon.

5. A method for preparing the composite material energy-saving door and window profile according to any one of claims 1 to 4, characterized in that: The steps include: Step S1, mixing the other raw materials except the fiber yarn uniformly by weight to obtain a mixed material, and dispersing the mixed material in an organic solvent to obtain a resin glue solution; Step S2, weaving the fiber yarn through a weaving machine according to a preset profile structure; Step S3, immersing the woven fiber cloth into the resin glue solution to perform resin injection; Step S4, hardening: hardening the fiber cloth injected with resin through a mold at high temperature; Step S5, molding: cutting, grinding, assembling and gluing the hardened fiber cloth in sequence.

6. The method for preparing the composite material energy-saving door and window profile according to claim 5, characterized in that: The mass ratio of the mixed material and the organic solvent in step S1 is (0.8-1.2):1; the organic solvent in step S1 is at least one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide; the high temperature hardening treatment in step S4 is specifically: keeping warm at 95-125°C for 2-6h, and then keeping warm at 175-185°C for 0.8-3h.

Citation Information

Patent Citations

  • A composite material energy-saving door and window profile

    CN110094137B

  • Environment-friendly anti-aging fiber reinforced composite material and preparation method thereof

    CN115304914A

  • FRP profile composite material and preparation method thereof

    CN115558231A